2020
DOI: 10.1111/jcmm.15877
|View full text |Cite
|
Sign up to set email alerts
|

RAD51AP1 promotes progression of ovarian cancer via TGF‐β/Smad signalling pathway

Abstract: Ovarian cancer (OC) is one of the leading causes of female deaths. However, the molecular pathogenesis of OC has still remained elusive. This study aimed to explore the potential genes associated with the progression of OC. In the current study, 3 data sets of OC were downloaded from the GEO database to identify hub gene. Somatic mutation data obtained from TCGA were used to analyse the mutation. Immune cells were used to estimate effect of the hub gene to the tumour microenvironment. RNA‐seq and clinical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…In addition, suppression of RAD51AP1 by siRNA reduced cell proliferation of ovarian cancer (OvCa) cells in vitro [3]. Confirmatory data and emerging evidence for the oncogenic potential of RAD51AP1 in other cancers is strengthening the relevance of this molecule [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, suppression of RAD51AP1 by siRNA reduced cell proliferation of ovarian cancer (OvCa) cells in vitro [3]. Confirmatory data and emerging evidence for the oncogenic potential of RAD51AP1 in other cancers is strengthening the relevance of this molecule [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 80%
“…For example, we have shown potential involvement of mTOR signaling in OvCa, whereas Zhao et al have shown a relationship between RAD51AP1 and in transforming growth factor β (TGF-β)/Smad signaling pathway. Using scatter plots, a significant positive correlation between RAD51AP1 with SMAD2-4 and TGFBR1 was observed [5]. This can be of increasing importance in OvCa, given that TGF-β can exert pro-tumorigenic effects, involving epithelial-mesenchymal transition (EMT) [16].…”
Section: Discussionmentioning
confidence: 96%
“…CCK-8 assay and plate clone formation assay are used to evaluate cell proliferation. CCK-8 assay is performed according to our previous study ( Zhao et al, 2020 ). After transfecting siRNA for 24 h, A2780 cells are cultured in six-well culture plates (1,000/well) for 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction and RT-qPCR are conducted according to our previous study ( Zhao et al, 2020 ). The primer sequences are listed in Supplementary Table 3 .…”
Section: Methodsmentioning
confidence: 99%
“…IGF2BP2 enhances circ0000745 and promotes aggressiveness and stemness in OC via miR-3187-3p/ERBB4/PI3K/AKT axis [ 122 ]. By TCGA analysis, down-regulation of RAD51AP1 (RAD51‐dependent homologous recombination) supressed proliferation, migration and invasion of OC cells and correlated with TGF-β/Smad pathway [ 123 ]. Under platinum and paclitaxel (PT) treatment, SFPQ/p54 nrb /SRSF2 pathway plays a crucial role in OC resistance [ 103 ].…”
Section: Influences Of Rbps On Regulating Oc Cellular Signalling Pathwaysmentioning
confidence: 99%